The Consensus Definition of Bronchopulmonary Dysplasia Is an Adequate Predictor of Lung Function at Preschool Age - Rite, Segundo; Martín de Vicente, Carlos; García-Iñiguez, Juan P.; Couce, María L.; Samper, María P.; Montaner, Alicia; Ruiz de la Cuesta, Carmen (Frontiers in Pediatrics, 2022)
Background: Recent attempts to refine the definition bronchopulmonary dysplasia (BPD) have based its predictive capacity on respiratory outcome in the first 2 years of life, eliminating the pre-existing requirement of 28 days of oxygen therapy prior to 36 weeks postmenstrual age (PMA). The objective of this study was to assess the utility of the 2001 consensus definition in predicting impaired lung function at preschool age. Methods: This cohort study included children aged 4–6 years old who were born at gestational age (GA) <32 weeks or bodyweight <1500 g. Univariate and multivariate analyses were performed to assess differences in antenatal and neonatal variables between BPD and non-BPD children. All participants underwent incentive spirometry. Lung function parameters were contrasted with the Global Lung Function Initiative (GLI-2012) reference equations and, together with antenatal and neonatal variables, compared among the different subgroups (no BPD, mild BPD, and moderate-to-severe BPD). A multivariate model was generated to identify independent risk factors for impaired lung function. Results: GA, hemodynamically significant patent ductus arteriosus, and late sepsis were independent risk factors for the development of BPD. A total of 119 children underwent incentive spirometry. All lung function parameters were significantly altered relative to reference values. Greater impairment of lung function was observed in the mild BPD versus the no BPD group (forced expiratory volume in the first 0.75 seconds [FEV0.75]: -1.18 ± 0.80 vs -0.55 ± 1.13; p=0.010), but no difference in forced vital capacity (FVC) was observed (-0.32 ± 0.90 vs -0.18 ± 1; p=0.534). The moderate-to-severe BPD group exhibited the most severe FEV0.75 reduction (FEV0.75: -2.63 ± 1.18 vs -0.72 ± 1.08; p=0.000) and was the only condition with FVC impairment (FVC: -1.82 ± 1.12 vs -0.22 ± 0.87; p=0.000). The multivariate analysis identified a diagnosis of moderate-to-severe BPD as an independent risk factor for lung function impairment. Conclusion: The 2001 consensus definition of BPD has adequate predictive capacity for lung function measured by spirometry at 4–6 years of age. Moderate-to-severe BPD was the best predictor of respiratory impairment. Children with mild BPD showed greater alteration of FEV0.75 than those without BPD.